2022
DOI: 10.3389/fimmu.2022.912583
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor RUNX3 Mediates Plasticity of ThGM Cells Toward Th1 Phenotype

Abstract: GM-CSF-producing T helper (Th) cells play a crucial role in the pathogenesis of autoimmune diseases such as multiple sclerosis (MS). Recent studies have identified a distinct population of GM-CSF-producing Th cells, named ThGM cells, that also express cytokines TNF, IL-2, and IL-3, but lack expression of master transcription factors (TF) and signature cytokines of commonly recognized Th cell lineages. ThGM cells are highly encephalitogenic in a mouse model of MS, experimental autoimmune encephalomyelitis (EAE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
(85 reference statements)
1
6
0
Order By: Relevance
“…To corroborate the identity of ThGM cells, we quantified the mRNA levels of Twist‐related protein 1 (TWIST1), transcriptional regulating factor 1 (TRERF1), musculin (MSC) and peroxisome proliferator‐activated receptor gamma (PPARγ), all of which are ThGM‐associated transcription factors 22 . As indicated in Figure S4, ThGM cells (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To corroborate the identity of ThGM cells, we quantified the mRNA levels of Twist‐related protein 1 (TWIST1), transcriptional regulating factor 1 (TRERF1), musculin (MSC) and peroxisome proliferator‐activated receptor gamma (PPARγ), all of which are ThGM‐associated transcription factors 22 . As indicated in Figure S4, ThGM cells (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, we found that live aortic ThGM cells were enriched in CD4 + CCR6 − CCR8 − CXCR3 − CCR10 + T cells, consistent with former reports. 10,22 We are the first to report the existence of ThGM cells in atherosclerotic aortas. Notably, ThGM-associated transcription factors such as TWIST1, TRERF1, MSC and PPARγ were highly expressed by these cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations